PKU for MI Muhammadiyah Butuh Senden, Magelang Regency through educative teaching aids - Ahwy Oktradiksa; Minzani Aufa (Community Empowerment, 2022)
MI Muhammadiyah (MIM) Butuh Senden was established in 1954 and has 119 students and 8 teachers. Despite the fact that it has been in existence for half a century, there are still a number of challenges, including 1) a lack of learning media resources in the form of educative teaching aids, which have an impact on the learning process; and 2) a lack of moral and material support from stakeholders in madrasah development. This program aims to improve the quality of madrasas by assisting teachers in the creation of educational teaching aids. The method is based on a community empowerment model (Participatory Rural Appraisal). Teachers' understanding and awareness of the importance of media in facilitating the teaching and learning process in the classroom has improved as a result of this program. Teachers correct each other for the resulting educational aids in this activity so that their use is more targeted and effective.